2007
DOI: 10.1002/gcc.20417
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and translocation of 3q26 with overexpression of EVI1 in Fanconi anemia‐derived childhood acute myeloid leukemia with biallelic FANCD1/BRCA2 disruption

Abstract: Fanconi anemia (FA) is an inherited disease with congenital abnormalities and an extreme risk of acute myeloid leukemia (AML). Genetic events occurring during malignant transformation in FA and the biology of FA-associated AML are poorly understood, but are often preceded by the development of chromosomal aberrations involving 3q26-29 in bone marrow of FA patients. We report here the molecular cytogenetic characterization of FA-derived AML cell lines SB1685CB and SB1690CB by conventional and array comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…by guest www.bloodjournal.org From AML cell lines derived from an FA patient of the particular D1/BRCA2 downstream group. 42 Here, break-apart FISH found frequent EVI1 duplication, as expected from the CGH/SNP array data, but no direct involvement in a fusion gene resulting from a translocation. Therefore, the potential role of EVI1 in the MDS/ AMLs with 3qϩ in typical FA-core patients remains elusive.…”
Section: Discussionsupporting
confidence: 69%
“…by guest www.bloodjournal.org From AML cell lines derived from an FA patient of the particular D1/BRCA2 downstream group. 42 Here, break-apart FISH found frequent EVI1 duplication, as expected from the CGH/SNP array data, but no direct involvement in a fusion gene resulting from a translocation. Therefore, the potential role of EVI1 in the MDS/ AMLs with 3qϩ in typical FA-core patients remains elusive.…”
Section: Discussionsupporting
confidence: 69%
“…The FA-derived AML cell line SB1690CB, which expresses high levels of EVI1, and the EVI1 negative AML cell line OCI-AML5 were maintained as described previously (10). HEK293T cells and Rat1 fibroblasts were used as previously described (28).…”
Section: Methodsmentioning
confidence: 99%
“…In acute myeloid leukemia (AML) high EVI1 expression is associated with poor response to cytotoxic treatment and adverse outcome (6,7). EVI1 overexpression has been linked to leukemic transformation in children undergoing gene therapy (8), and individuals affected by Fanconi Anaemia (FA), which is an inherited DNA damage response defect with cancer predisposition (9,10). High EVI1 expression conferring resistance to cytotoxic treatment and poor prognosis is also seen in other malignancies (11–14).…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the presence of putative EVI1-binding sites indicated that these were EVI1 target genes, we first performed HELP analysis on the human AML SB1690CB cell line, carrying a chromosomal 3q26 aberration and overexpressing EVI1 23 . A highly significant concordance of hypermethylated genes (89%) was found between the SB1690CB cell line and the hypermethylated genes identified in the EVI1 AML patient samples (211/238 genes; supplemental Table 5).…”
Section: A Role For Evi1 In Promoter Hypermethylation In Evi1 Amlmentioning
confidence: 99%